A predictive model for the performance of the ejector in refrigeration system. (15th October 2017) - Liu, Jiapeng; Wang, Lei; Jia, Lei
Highlights: A simple model is proposed to predict the performance of the ejector in refrigeration system. The proposed model only has four unknown parameters which can be determined by the traditional identification methods easily. Literature and experimental data are used to validate the accuracy of the proposed model. Comparison result shows that the proposed model is more accuracy and simpler than the previously published models. Abstract: Ejectors are widely used in the refrigeration system and the evaluation of the ejector performance is important for the refrigeration system real time control. In this paper, a simple model is proposed to predict the performance of the ejector in the refrigeration system. A theoretical model is developed based on the thermodynamic principles and ideal gas property firstly. And then the proposed model is simplified to linear equations with four unknown parameters which can be determined by traditional identification methods easily. The accuracy of the model is validated by literature and experimental data. The results show that the model has a strong ability to predict the ejector entrainment ratio and critical back pressure. Furthermore, the proposed method is more accuracy and simpler than the previously published models. It is hoped that the proposed model is useful for the real time control of the ejector refrigeration system.